Numerical simulation of extremely severe corrosion of the STK400 graded steel pipe pile in Southern Vietnam’s brackish environment: effects on macrocell corrosion of seawater flow and tide - Ngoc-Thanh Pham; Vinh-Dat Vuong; Toan Viet Tran; Thang Van Le; Anh Quang Vu (Materials Research Express, 2022)
In the recent work, a field test in which an STK400 steel pipe pile was vertically driven into the sea bed was conducted in Southern Vietnam’s brackish environment. After 5 years of exposure, the steel pipe pile was uniformly corroded in the immersion zone but two penetrated holes (formed a 152° central angle) appeared near the low water level. This severe corrosion can not be explained experimentally. Therefore, two numerical models have been individually built to calculate the corrosion distribution on a steel pipe pile surface. The results of these models help to explain this observation. The differential aeration due to the tidal condition and seawater flow is confirmed to be the cause of this field test observation. The first model accounting for the effects of tide shows that a macroscopic corrosion cell (along the pipe length) is formed. The cathodic kinetics are only strongly enhanced near the seawater surface (which changes over time and belongs to the tidal condition) while the rest is controlled by the limited-diffusion phenomenon. Therefore, a cathode is formed underneath the seawater surface and receives a protective current from the deeper steel surface (acts as an anode) where these two holes may appear. The second model considering the effects of seawater flow successfully locates two highly active anodic areas being in agreement with the position of the two penetrated holes observed in the field test.